Novel N-Pyrrolylcarboxylic Acid Derivative as a Potential New Analgesic and Anti-Inflammatory Drug - Hristina Zlatanova; Stanislava Vladimirova; Ilia Kostadinov; Delian Delev; Tanya Deneva; Ivanka Kostadinova; Atanas Bijev (International Journal of Pain Management, 2017)
The objective of our study was to evaluate the analgesic and anti-inflammatory activity, as well as possible organ toxicity of 2-3-3-methyl-pentanoic acid (compound 3d), a newly synthesized pyrrolic derivative, structurally similar to Celecoxib. Antinociception was assessed using animal pain models with thermal and chemical stimuli (paw withdrawal, tail-flick and formalin test). Anti-inflammatory activity was measured using the carrageenan-induced paw edema model. Blood samples were collected from the animals to study possible organ toxicity. All experiments were performed on male Wistar rats. The results in our study show that in experimental conditions 2-3-3-methyl-pentanoic acid has analgesic action against thermal and chemical stimuli. This effect is registered after both single and multiple administration of the compound. In the carrageenan model after single administration compound 3d did not inhibit formation of paw edema. After multiple administration all doses of compound 3d significantly suppressed paw edema at second, third and fourth hours. Hematological tests showed that compound 3d did not affect red blood cells and platelets but decreased white blood cell levels and the highest used dose decreased hemoglobin as well. Compound 3d decreased blood sugar levels and liver transaminases, compared to the control. Compound 3d did not affect creatinine levels but the smallest dose used lowered blood urea. We concluded antinociception in the tested compound is most likely mediated by supraspinal, spinal and peripheral mechanisms. Possible tolerance develops towards the analgesic action on spinal level after continuous administration. Anti-inflammatory activity, though significant, is probably not the leading cause for antinociception.
Keywords: pyrrolic core